2020
DOI: 10.1101/2020.12.29.424785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human blood contains circulating cell-free mitochondria, but are they really functional?

Abstract: Dache et al. (2020, FASEB J. 15, e2002338–15) recently reported the presence of respiratory-competent cell-free mitochondria in human blood (up to 3.7 x 106 per mL of blood), providing exciting perspectives on the potential role of these extra-cellular mitochondria. While their evidence for the presence of cell-free mitochondria in human blood is compelling, their conclusion that these cell-free mitochondria are respiratory-competent or functional has to be re-evaluated. To this end, we evaluated the functiona… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Similarly, the expression of cytochrome c oxidase subunit 4 (COX-IV), the final enzyme in the respiratory electron transport chain, was not affected in PMN treated with free-Mitos, whereas DAMPs treatments induced a 4.8-fold increase in COX IV levels when compared to vehicle control (Fig 1G and H). These results indicate that despite their uptake by PMN, freeMitos do not modulate the oxygen consumption rate (OCR) of PMN, further supporting evidence that freeMitos may not convey respiratory competent mitochondria to recipient cells (Al Amir Dache et al, 2020;Stier, 2021).…”
Section: Effect Of Freemitos On the Respiratory State Of Pmnmentioning
confidence: 56%
“…Similarly, the expression of cytochrome c oxidase subunit 4 (COX-IV), the final enzyme in the respiratory electron transport chain, was not affected in PMN treated with free-Mitos, whereas DAMPs treatments induced a 4.8-fold increase in COX IV levels when compared to vehicle control (Fig 1G and H). These results indicate that despite their uptake by PMN, freeMitos do not modulate the oxygen consumption rate (OCR) of PMN, further supporting evidence that freeMitos may not convey respiratory competent mitochondria to recipient cells (Al Amir Dache et al, 2020;Stier, 2021).…”
Section: Effect Of Freemitos On the Respiratory State Of Pmnmentioning
confidence: 56%
“…The authors provided an evaluation of 200,000 up to 3,700,000 respiratory-competent mitochondria per ml of extracted plasma, and suggested that circulating cell-free respiratory-competent mitochondria could represent a novel class of signaling organelles involved in regulatory activities and intercellular communication. Although the evidence for the presence of cell-free mitochondria in human blood is convincing, the conclusion that these mitochondria are energy competent or functional for respiration has been more recently refuted [ 140 ]. In its report, Stein evaluated the functionality of cell-free mitochondria in human blood using high-resolution respirometry and mitochondria extracted from platelets from the same blood samples as positive controls.…”
Section: Extracellular Mitochondria: Active Players In Health and Diseasementioning
confidence: 99%
“…Additionally, the presence of circulating cell-free mitochondria in blood may serve as an alternative matrix for the biomarkers discussed above. Cell-free mitochondria are the presence of whole and functioning mitochondria out of the cell, which has been detected within human blood [ 56 •, 57 ]. In addition to whole mitochondria, cell-free mtDNA fragments are also detected in human blood, either encapsulated within extracellular vesicles or free-circulating.…”
Section: Mitochondrial Biomarkers For Environmental Healthmentioning
confidence: 99%